Uncovering the dynamic relationship between intrinsic motivation and basic softball skills: An exploratory analysis - Ibrahim, Charisma Azizah; Mudjihartono; Sumpena, Asep; Gumilar, Agus (UIR Press, 2023)
Physical education (PE) is a pivotal domain, offering students valuable opportunities for excelling in multiple sports performances when harmonized with contemporary curricula that emphasize cognitive engagement through intrinsic motivation. This blend has the potential to enhance not only softball skills but also performance across various sports. This study investigated the relationship between intrinsic motivation (interest, enjoyment, and personal challenge) and fundamental softball performance skills among 30 active students (F = 15; M = 15) enrolled in the Indonesian University of Education’s physical education program. It employed an ex post facto research design and quantitative method, utilizing the Sport Motivation Scale (SMS) (0.779 > 0.05) and O’Donnell Softball Test (0.701 > 0.05), both instruments demonstrated good reliability and validity. Results from data analysis in IBM SPSS 25.0, reveal that interest and enjoyment moderately correlate but lack of significant impact softball skills. However, personal challenge shows a strong positive correlation with interest and enjoyment. Although personal challenge does not directly influence softball skills, it plays a crucial role in fostering interest and enjoyment in sports. Understanding intrinsic motivation's impact on skill development can inform effective teaching methods and encourage greater engagement in physical activities for improved overall well-being. This research provides insights for educators and coaches to design learning experiences that incorporate challenges and promote intrinsic motivation, enhancing students’ engagement and skill development in physical education activities. Future research could explore intrinsic motivation's impact on softball skills across diverse skill levels, considering factors like the learning environment, individual differences, and coaching styles for optimized skill development.